2018
DOI: 10.1002/bab.1680
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol‐mediated regulation of hepatic iNOS in obese rats: Impact of Src, ERK1/2, AMPKα, and miR‐221

Abstract: This study aimed to investigate in vivo effects of estradiol on the regulation of hepatic inducible nitric oxide synthase (iNOS) expression in the high fat (HF) diet-induced obesity. Also, we aimed to investigate whether activation of the extracellular signal-regulated kinase (ERK1/2), adenosine monophosphate-activated protein kinase (AMPK), Src kinase, and miR-221 is involved in estradiol-mediated regulation of iNOS in the liver of obese male Wistar rats. Male Wistar rats were fed a standard laboratory diet o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 91 publications
(107 reference statements)
0
3
0
Order By: Relevance
“…In support of this hypothesis, studies in rodents suggested that these observed deleterious aging-related effects on females’ livers might be attributed to impaired lipid metabolism. In fact, in these models, estrogens increased fatty acid β-oxidation by AMPK activation [32,33]. Taking together these studies, it could be speculated that in menopausal women, lower serum estrogen levels might constitute a major cause for impaired lipid accumulation/break down balance and therefore for the promotion of NAFLD development.…”
Section: Introductionmentioning
confidence: 99%
“…In support of this hypothesis, studies in rodents suggested that these observed deleterious aging-related effects on females’ livers might be attributed to impaired lipid metabolism. In fact, in these models, estrogens increased fatty acid β-oxidation by AMPK activation [32,33]. Taking together these studies, it could be speculated that in menopausal women, lower serum estrogen levels might constitute a major cause for impaired lipid accumulation/break down balance and therefore for the promotion of NAFLD development.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is a foremost underlying risk factor of several chronic diseases, including metabolic syndrome (MS), T2DM, cardiovascular diseases, fatty liver diseases, and cancer [16][17][18][19][20][21][22][23][24], all of which share a common pathological condition, insulin resistance (IR) [25]. Fat accumulation in the visceral tissues and organs in obesity leads to free fatty acids (FFAs) release into the portal circulation and further impairment of glucose metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…It is considered that the spread of NAFLD in the coming decade may increase, and by 2030, it will be the most common reason of liver transplantation [4]. NAFLD is the most prevalent chronic liver disease (CLD) [5] and includes a set of different histological features from simple steatosis to nonalcoholic steatohepatitis (NASH), that finally leads to cirrhosis and hepatocellular carcinoma [6]. Despite the fact that NAFLD is powerfully related with insulin resistance and obesity, its pathogenesis has not been explained clearly [7].…”
Section: Introductionmentioning
confidence: 99%